Preventing delayed cracks in deep drawing processes of SUS304 cylindrical cups using a coated die / Phoo Yoong Hau - Phoo, Yoong Hau (2019)
Longitudinal delayed cracks tend to form along the sidewall of fully drawn SUS304 metastable austenitic stainless steel cylindrical cups immediately after the deep drawing process for a certain incubation period ranging from several minutes to several days. Although the delayed cracks were eliminated with a polished and uncoated die using nano-lubrication under elevated blank holding forces (BHF) in a previous study, the crack-free BHF range was too narrow and the magnitude was too high. In this study, the crack-free BHF range has been successfully reduced from 29kN-31kN to 5kN-10kN using a Titanium Nitride (TiN) coated drawing die under conventional lubrication. The high concentration of deformation-induced martensite in the thickened valley points along the cup edge resulting from the high circumferential compressive stress during the drawing process increases the chances for the delayed cracks. The elimination of the delayed cracks was attributed to the reduce in amount of wall thickening, increase in valley heights and the low circumferential tensile residual stress along the cup edge. The experimental results showed that delayed cracks were observed in cups formed with the polished and uncoated die when the average amount of wall thickening in the valley points exceeded 33.5% within the BHF limits from 5kN-15kN. The cracks were prevented for 28% of wall thickening under the BHF of 12kN using the same die. However, no delayed cracks were observed in the cups formed with the TiN coated die within the BHF limits from 5kN-10kN. Because the average amount of wall thickening in the valley points of these cups ranged from 24.5%-32.7%, lower than the wall thickening limit for crack i.e. 33.5%. The valley height that more than 33mm for coated and uncoated die make the cup free from delayed crack, while the other cup with valley height lower than 33mm were suffer from delayed crack. The TiN-coated die has a lower average surface roughness (Ra=0.382?m) than the polished uncoated die (Ra=0.581?m), provides a lower frictional force path for the flow of blank material into the die and largest elongation as possible. Besides that, the small BHF values were always desired as the higher risk for fracture of the cup with larger BHF value. The widest crack free BHF range was desired due to the part can be formed with any values of BHF within the range in order to achieve desired objectives.